'Lost in translation': United Nations commentaries on gender stereotypes to Muslim countries. Issue 2 (7th February 2023) - Kertcher, Chen; Turin, Ornat
ABSTRACT: The majority of writing on global human rights diffusion focuses on the state level and state's rejection or assimilation of such norms. This paper turns the focus to the international level and to the norm gatekeeper, the UN Committee on the Elimination of Discrimination against Women, CEDAW. The study examines how CEDAW translates the mission of eradication of negative stereotypes. The analysis is based on close reading of UN policy documents defining the concept of stereotypes, and a content analysis of 55 commentary reports addressed to Muslim states from 2010 to 2019. The paper identified three main obstacles to an effective process: the UN's emphasis on the behavioural manifestation of stereotypes instead of confronting social perceptions; the commentary reports' use of vague and superficial terminology that fails to operationalise eradication of stereotypes; and a deficiency of positive social and cultural models that inhibits a vision for a world devoid of stereotypes. To conclude, CEDAW condones the presence of negative stereotypes but at the same time avoids translating its mission into clear applicable action.